The role and contribution of civil society and community actors in COVID-19 prevention and control: the case of the COMVID COVID-19 movement in Burkina Faso - Sory, Orokia; Kiendrébéogo, Joël; Kafando, Yamba; Kaboré, Issa; Tapsoba, Charlemagne; Kaboré, Simon; Mbaye, Seyni; Touré, Cheickna (BMJ global health, 2023)
Communities should play a crucial role in the fight against public health emergencies but ensuring their effective and sustained engagement remains a challenge in many countries. In this article, we describe the process of mobilising community actors to contribute to the fight against COVID-19 in Burkina Faso. During the early days of the pandemic, the national COVID-19 response plan called for the involvement of community actors, but no strategy had been defined for this purpose. The initiative to involve community actors in the fight against COVID-19 was taken, independently of the government, by 23 civil society organisations gathered through a platform called ‘Health Democracy and Citizen Involvement (DES-ICI)’. In April 2020, this platform launched the movement ‘Communities are committed to Eradicate COVID-19 (COMVID COVID-19)’ which mobilised community-based associations organised into 54 citizen health watch units (CCVS) in Ouagadougou city. These CCVS worked as volunteers, performing door-to-door awareness campaigns. The psychosis created by the pandemic, the proximity of civil society organisations to the communities and the involvement of religious, customary and civil authorities facilitated the expansion of the movement. Given the innovative and promising nature of these initiatives, the movement gained recognition that earned them a seat on the national COVID-19 response plan. This gave them credibility in the eyes of the national and international donors, thus facilitating the mobilisation of resources for the continuity of their activities. However, the decrease in financial resources to offset the community mobilisers gradually reduced the enthusiasm for the movement. In a nutshell, the COMVID COVID-19 movement fostered dialogues and collaboration among civil society, community actors and the Ministry of Health, which plans to engage the CCVS beyond the COVID-19 response, for the implementation of other actions within the national community health policy.